2014
DOI: 10.1039/c3sm51640g
|View full text |Cite
|
Sign up to set email alerts
|

Buckling, symmetry breaking, and cavitation in periodically micro-structured hydrogel membranes

Abstract: We investigated swelling induced instabilities in porous membranes with a square array of micron-sized circular holes prepared from a pH and temperature dual-responsive hydrogel, poly(2-hydroxyethyl methacrylate-co-N-isopropylacrylamide-co-acrylic acid) (PHEMA-co-PNIPAAm-co-PAA). At room temperature (25 °C), the hydrogel swelled to ∼1.5 to 8 times of its dried volume when pH was increased from 2 to 7. Within this regime, we observed four distinctive morphologies of the hydrogel membrane, including a "breathing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Beyond the instability threshold, rapid and dramatic changes of the structural geometry occur, and a careful design of the initial architecture may lead to the formation of new and homogeneous periodic patterns [159][160][161][162]. Interestingly, it has been recently shown that such dramatic geometric rearrangements induced by instabilities can be exploited to rapidly tune the macroscopic response and functionalities of the structures [22,34,[163][164][165][166][167][168][169][170][171][172][173][174].…”
Section: Instability-driven Pattern Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the instability threshold, rapid and dramatic changes of the structural geometry occur, and a careful design of the initial architecture may lead to the formation of new and homogeneous periodic patterns [159][160][161][162]. Interestingly, it has been recently shown that such dramatic geometric rearrangements induced by instabilities can be exploited to rapidly tune the macroscopic response and functionalities of the structures [22,34,[163][164][165][166][167][168][169][170][171][172][173][174].…”
Section: Instability-driven Pattern Formationmentioning
confidence: 99%
“…11). Moreover, while in most of the cases mechanical loading is used to deform the structures and trigger the instabilities, it has also been shown that other stimuli including swelling [160,[165][166][167][168]183] (see Fig. 12(a)), capillary pressure [172] (see Fig.…”
Section: Instability-driven Pattern Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently and in a different vein, identification and elucidation of pathways by which achiral building blocks spontaneously organize to create chiral structures have become an area of active study. Examples of these pathways include packing with multiple competing length scales (8-10, 23, 24), reconfiguration through mechanical instabilities of periodic structures (20,25,26), and helix formation of flexible cylinders through inter-and intracylinder interactions (27,28). In addition, the system of a broken chiral symmetry often consists of domains of opposite handedness with defects separating the domains.…”
mentioning
confidence: 99%
“…Thus, the deformation of a dielectric elastomer links a voltage to a force [26], the deformation of a hydrogel links a change in acidity in a solution to a change in the focal length of a lens [27], the swelling of an elastomer seals an oil well for hydraulic fracture [28,29], and the deformation of a gel and an elastomer enables ionic music and ionic skin [30,31]. Soft materials can be fabricated with feature sizes as small as several micrometers [32][33][34][35] and moduli as low as ~00Pa 1 [35][36][37]. It is conceivable that optical forces will enable devices of soft materials, complex shapes, and small features.…”
Section: Introductionmentioning
confidence: 99%